Renewable energy driven adsorption cooling system - Yap, Immanuel Siong Seng (Nanyang Technological University, 2023)
The purpose of air-conditioning is to cool and dehumidify the air to provide comfortable indoor air quality. The purpose of this project is to design a chiller that utilizes environmentally friendly refrigerants, powered by renewable energy. Water is the refrigerant to be considered due to its relatively high latent heat of vaporization. This report focuses on an adsorption cooling system driven by renewable energy, capable of dehumidification. The mass and energy balances for each component of adsorption cooling system are derived from the rigor of classical thermodynamics. Mathematical modelling is performed through MATLAB coding to calculate the performances in terms of cooling capacity, absolute humidity. The simulation results are based on experimentally confirmed isotherms and kinetics data. This report also explains the working principles of cooling cum dehumidification system. The performance factors such as the specific cooling power (SCP), the coefficient of performance (COP) and the humidity ratio are calculated for various cycle times and heating source temperatures. The simulation uses MOFs such as AQSOA-Z01, AQSOA-Z02, AQSOA-Z05, MIL101(Cr), MOF801 and Al-Fum, that has the SCP value of 0.11kW/kg, 0.0068kW/kg, 0.028kW/kg, 0.0002kW/kg, 0.117kW/kg, 0.019kW/kg and COP of 0.067, 0.005, 0.025, 0.0001, 0.067, 0.009 respectively